International Council for Standardization in Haematology Guidance for New Lot Verification of Coagulation Reagents, Calibrators, and Controls - Gosselin, Robert C.; Castellone, Donna; Dorgalaleh, Akbar; Hickey, Kieron; Lippi, Giuseppe; Moffat, Karen; O'Toole, Rebecca; Rigano, Joe (Seminars in Thrombosis and Hemostasis, 2023)
The clinical laboratory uses commercial products with limited shelf life or certain expiry dates requiring frequent lot changes. Prior to implementation for clinical use, laboratories should determine the performance of the new reagent lot to ensure that there is no significant shift in reagent performance or reporting of patient data. This guideline has been written on behalf of the International Council for Standardization in Haematology (ICSH) to provide the framework and provisional guidance for clinical laboratories for evaluating and verifying the performance of new lot reagents used for coagulation testing. These ICSH Working Party consensus recommendations are based on good laboratory practice, regulatory recommendations, evidence emerged from scientific publications, and expert opinion and are meant to supplement regional standards, regulations, or requirements.
Keywords: new lot reagent verification; coagulation testing; laboratory